Fluctuations in stratification and nutrient dynamics during the pre-bloom period in a Western margin of the East sea - Hae Kun Jung; Changsin Kim; Beom Sik Kim; Jeong Hee Shim; In Seong Han; Chung Il Lee; Dongyoung Kim (Scientific Reports)
Abstract Stratification is a fundamental process influencing nutrient availability and biological productivity in coastal marine ecosystems. In this study, we examine multi-decadal variability in winter stratification and nutrient distribution within Western margin of the East Sea (WES), using observational data collected between 1990 and 2023. Stratification characteristics were quantified using the Brunt-Väisälä frequency (N²), with particular focus on changes in intensity and the depth of maximum stratification. These variables were then analyzed in relation to environmental factors such as upper-layer temperature, surface wind speed, and East Korea Warm Current (EKWC) transport. Over the study period, stratification intensity increased at an average rate of 1.1% per year, while the maximum stratification depth shoaled by approximately 0.6% annual trends that became more pronounced after 2015. These shifts were closely linked to enhanced thermal stratification and increased EKWC volume transport. Enhanced stability of the water column was accompanied by reduced vertical mixing, which in turn intensified the nitrate gradient between surface and subsurface waters. The most marked nitrate accumulation was observed near 100 m, where stratification was strongest. This study highlights how physical oceanographic changes during winter can regulate nutrient supply prior to the spring bloom, potentially influencing seasonal productivity in marginal seas. The results emphasize the importance of long-term monitoring of vertical structure in assessing the ecological impacts of ocean variability.